Managed aquifer recharge applications for climate adaptation in developing countries: mounting evidence, abundant potential - International Water Management Institute (International Water Management Institute, 2024)
Four case studies from Africa and Asia demonstrate that managed aquifer recharge can help developing countries adapt to climate change.